Felix von Bärensprung—A Review of His Life and Work on the Occasion of His 200th Birthday. (April 2023) - Weyers, Wolfgang
Abstract: Felix von Bärensprung was a pioneer of dermatopathology. His monograph of 1848, "Contributions to the Anatomy and Pathology of the Human Skin, " was one of the first publications on that subject. Von Bärensprung also described and named erythrasma, elucidated the pathogenesis of herpes zoster, contributed a comprehensive review of the history of dermatology in an unfinished textbook of skin diseases, and was coauthor, together with Ferdinand Hebra of Vienna, of one of the most influential clinical atlases in the history of dermatology. The 200th anniversary of his birthday in 2022 provides an occasion for reminding of one of the leading dermatologists of the mid 19th century.